Gravel lining for improved management - Valera, A.; Misra, V. S.; Durga Bahadur, K.C. (1993)
Aquatic weed infestation of irrigation canals reduces irrigation canal capacity and retards flow, delaying timely irrigation water deliveries. An experiment on gravel lining was conducted in the Banganga River Irrigation System. This irrigation system is located in the western plain of Nepal with a command area of 6,000 ha. There were 3 treatments used in this experiment, namely: without lining, mixed gravel and graded gravel. Three sections of the main canal were selected where weed infestation was prevalent and monitored for weekly weed growth. After 14 weeks, the average weed population density for the unlined treatment was 55 weed plants per square meter (w/m) while the graded gravel lining had 16 w/m and the mixed gravel lining had only 3 w/m. The actual costs of the experiment except monitoring of lining these canals sections was only 153 Nepalese rupees (USD $ 3.3) per cubic meter of gravel lined canal. The experiment showed the effectiveness of mixed gravel lining in suppressing the growth of aquatic weeds in the main canal. Although the estimated costs showed significant savings for this lining, further examination of costs and investigation of the nature of the aquatic weeds are suggested.